The Relationship Between Use of Gadgets and Sleep Quality on Nursing Students - Andri Nugraha; santi, Santi Rinjani; Aceng Ali; Erwin Pardiansyah (Future Science, 2023)
Introduction: The proliferation of information and communication technology, particularly handheld electronic devices, has resulted in a significant portion of the population becoming ensnared in a perpetual reliance on smartphones. The prevalence of technological devices has led to a significant dependency among students. Approximately 30 million individuals, constituting approximately 80% of the user population in Indonesia, are students. This behaviour frequently leads individuals to lose track of time during late hours, as they habitually resort to incessantly monitoring their electronic devices as a means of evading social interactions on online platforms. The objective of this study was to investigate the correlation between gadget usage and sleep quality. Methods: The present study employed a quantitative approach utilizing a cross-sectional design. This study employed comparative statistical analysis to examine the correlation between gadget usage and the sleep quality of students at STIKes Karsa Husada Garut. Results:: The data analysis using the Chi-square test yielded a p-value of less than 0.05, suggesting a significant association between the utilization of Gadgets and the quality of sleep among nursing students at STIKes Karsa Husada Garut. Conclusion: the utilization of electronic devices had a notable impact on the sleep quality of final-year students at STIKes Karsa Husada Garut. A negative correlation can be interpreted as indicating an inverse relationship between the use of gadgets and sleep quality, such that an increase in gadget usage is associated with a decrease in sleep quality and vice versa.